AHP in Assessing Performance of Diploma Institutes – A Case Study - Goshal, Dr. Sujit Kumar; Naskar, Sukanta Kumar; Bose, Dr. Dipankar (Journal of Technical Education and Training, 2012)
Present paper shows application of Analytical Hierarchy Process (AHP) as potential tool in decision making in assessing performance of diploma institutes. Parameters for assessing diploma level institutes are used as example. A hierarchical structure is framed for the parameters and the diploma institutes from where feedback received against the parameters for this study. By applying the AHP, the parameters can be prioritized and a descending order list of diploma institutes can be made in order to identify the best performing institutes. A sensitivity analysis can be performed to check the sensitivity of the final selection (decision) to minor changes in the judgement. Step by step approaches for applying AHP will be used by using AHP Calculation Software by CGI (web-based free software). It is hoped that this will encourage the application of the AHP in assessing institutional performance of similar institutions.